The Urgency of Law Enforcement in Anticipating Pollution Caused by Corporate Offshore Exploration - Ida Wakhidatus Sholechah; Slamet Suhartono (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Introduction to the Problem: Offshore oil and gas exploration in Indonesia has expanded significantly to meet rising domestic and global energy demands. However, these activities pose serious risks of marine environmental pollution, and the existing legal framework proves inadequate for effective oversight and enforcement. Purpose/Study Objectives: This article aims to identify and evaluate regulatory deficiencies in offshore exploration governance and to propose targeted legal reforms to enhance environmental protection and enforcement. Design/Methodology/Approach: Adopting a normative legal methodology, this study critically examines current legislation and institutional practices, benchmarking them against stringent liability doctrines and international regulatory standards. Findings: The analysis reveals three principal regulatory shortcomings: (i) failure to apply strict liability principles; (ii) absence of mandatory environmental guarantee mechanisms; and (iii) institutional overlaps undermining coherent governance. In response, the study advocates (a) adopting unified sectoral legal instruments; (b) strengthening environmental oversight bodies; and (c) integrating progressive international regulatory frameworks. Legal reform is imperative to secure marine environmental protection, facilitate ecological restoration, and uphold justice for coastal communities, consistent with constitutional mandates and sustainable development principles. Paper Type: Research Article